1970
DOI: 10.1055/s-0028-1098457
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of Gastric Mucosa — Pathogenesis, Incidence and Classification of the Erosive Gastritis —

Abstract: We divided the erosive gastritis into two types, namely, the mature type and the immature type. The mucosal elevation consisted of fibrosis in the former type and of edema in the latter. The surrounding mucosal elevation is irreversible in the erosive gastritis of mature type, on the contrary, it is reversible in the immature type. It is difficult to differentiate these two types, however, it is possible by the repeated examination. The frequency rate of the erosive gastritis is hard to evaluate, however, taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

1974
1974
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 3 publications
1
7
0
2
Order By: Relevance
“…Eight of 14 polypoid lesions taken from the gastroenterostomy stoma of 14 patients by means of endoscopic polypectomy included submucosa and showed wide submucosal cystic glands. Similar appearances though of more limited extent, were encountered in three of 25 polypoid chronic erosions (the so-called 'mature' erosions of Kawai et al 1970) and in four adenomatous polyps endoscopically removed. The changes were also found in six out of 20 surgical specimens from patients operated upon for gastric cancer and in 16 out of 18 surgical gastric resections from patients previously operated upon for benign lesions and thereafter for post-anastomotic ulcer (14 cases) or for cancer of the gastric remnant (four cases).…”
Section: Introductionsupporting
confidence: 54%
“…Eight of 14 polypoid lesions taken from the gastroenterostomy stoma of 14 patients by means of endoscopic polypectomy included submucosa and showed wide submucosal cystic glands. Similar appearances though of more limited extent, were encountered in three of 25 polypoid chronic erosions (the so-called 'mature' erosions of Kawai et al 1970) and in four adenomatous polyps endoscopically removed. The changes were also found in six out of 20 surgical specimens from patients operated upon for gastric cancer and in 16 out of 18 surgical gastric resections from patients previously operated upon for benign lesions and thereafter for post-anastomotic ulcer (14 cases) or for cancer of the gastric remnant (four cases).…”
Section: Introductionsupporting
confidence: 54%
“…The recent report of Turner et al (1974) of aphthous ulceration in patients with antral gastritis is thus difficult to assess, as this study did not include histology. Others have described persisting erosions (Kawai et al, 1970). Roesch and Ottenjaun (1970) have attempted to classify gastric erosions, using endoscopic appearance and histology of gastric biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies in the English literature have focused on VG. An association with duodenal and gastric ulceration and a male predominance were reported in the 1970s [ 1 , 2 ]. In 2010, Yamamoto et al [ 3 ] reported an increasing risk of endoscopic erosive gastritis in adults with a low serum adiponectin level and high body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%